PENERAPAN MODEL PEMBELAJARAN BERBASIS LINGKUNGAN UNTUK MENGEMBANGKAN KETERAMPILAN PROSES SAINS DAN MENINGKATKAN HASIL BELAJAR KOGNITIF PADA SISWA KELAS X SMA MUHAMMADIYAH 1 METRO TAHUN PELAJARAN 2011/2012 - Nadiroh, Ayun; Susanto, Agus (UNIVERSITAS MUHAMMADIYAH METRO, 2012)
This study aimed to: 1) develop students science process skills class X2 SMA Muhammadiyah 1 Metro. 2) enhance students cognitive learning outcomes X2 class SMA Muhammadiyah 1 Metro. Subjects in this study were students SMA Muhammadiyah 1 X2-class Metro Lesson Year 2011/2012 on the subject matter of the world of plants (Plantae). The study was conducted on February 1 until March 7, 2012 to be implemented in two cycles. Each cycle of meetings held 3 times. The conclusion of the research are there was an increase from cycle I to cycle II . While the cognitive learning outcomes of students has increased from pre-PTK into the second cycle. In the pre-PTK is increased 60.6% to 65.3% in cycle I, and from cycle I is 65.3% increased to 77.2% in cycle II. Based on data from the study of learning with model-based learning environment to develop science process skills and improve cognitive learning outcomes in students, researchers therefore suggest to teachers to implement this model in the study of biological science.Â Kata Kunci: model pembelajaran berbasis lingkungan, keterampilan proses sains, hasil belajar kognitif